Kontribusi Faktor Fundamental Terhadap Return Saham Syariah Sektor Pertanian - Dian Nofianti; Alfiatul Maulida; Agus Dwi Cahya (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to analyze the influence of the Current Ratio (CR), Return on Equity (ROE), and Debt to Equity Ratio (DER) on stock return in Sharia companies listed on the Sharia Stock Index (ISSI) for the 2015-2019 period. The population used in this research was 11 companies. The data used in this research is secondary data. The sampling method used purposive sampling method and resulted in 9 companies. The data analyze technique uses multiple linear regression. The research results show that the variables Current Ratio, Return on Equity, and Debt to Equity Ratio simultaneously influence stock return. Partially, the Current Ratio variable has a positive and significant affect on stock return, Return on Equity has a positive and unsignificant affect on stock return, Debt to Equity Ratio has a positive and unsignificant effect on stock return.